ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Fattah, Nur Waina; Damayanti, Ratna Ayu; Idris, Muhammad Istiyansyah Ulman (APSSAI ACCOUNTING REVIEW, 2023)
The purpose of this research is to identify the relationship between the quality of local government financial reports and factors such as human resource competence, the use of accounting information systems, and internal control systems. In 2023, the Majene Regency's regional apparatus organization hosted this study. A total of 30 samples were used for this study's quantitative, causal approach. Each sample included two respondents. This study's questionnaire took the form of a declarative statement. In this study, multiple linear regression was employed to analyze the data. Analysis of the data demonstrates that the quality of local government financial reports is positively and significantly impacted by human resource competency, the implementation of accounting information technologies, and internal control systems.